Every Dog Has Its Data: Evaluation of a Technology-Aided Canine Rabies Vaccination Campaign to Implement a Microplanning Approach - Monroe, Benjamin; Ludder, Fleurinord; Dilius, Pierre; Crowdis, Kelly; Lohr, Frederic; Cleaton, Julie; Gamble, Luke; Blanton, Jesse; Etheart, Melissa; Pieracci, Emily G.; Natal Vigilato, Marco Antonio; Molina-Flores, Baldomero; et al. (Frontiers in Public Health, 2021)
Background: Robust dog vaccination coverage is the primary way to eliminate canine rabies. Haiti conducts annual canine mass vaccination campaigns, but still has the most human deaths in the Latin American and Caribbean region. We conducted an evaluation of dog vaccination methods in Haiti to determine if more intensive, data-driven vaccination methods, using smartphones for data reporting and geo-communication, could increase vaccination coverage to a level capable of disrupting rabies virus transmission. Two cities were designated into ‘traditional’ and ‘technology-aided’ vaccination areas. Traditional areas utilized historical methods of vaccination staff management, whereas Technology-aided areas used smartphone-supported spatial coordination and management of vaccination teams. Smartphones enabled real time two-way geo-communication between campaign managers and vaccinators. Campaign managers provided geographic instruction to vaccinators by assigning mapped daily vaccination boundaries displayed on phone handsets, whilst vaccinators uploaded spatial data of dogs vaccinated for review by the campaign manager to inform assignment of subsequent vaccination zones. The methods were evaluated for vaccination effort, coverage, and cost. A total of 11 420 dogs were vaccinated during the 14-day campaign. The technology-aided approach achieved 80% estimated vaccination coverage as compared to 44% in traditional areas. Daily vaccination rate was higher in traditional areas (41.7 vaccinations per team-day) compared to in technology-aided areas (26.8) but resulted in significantly lower vaccination coverages. The cost per dog vaccinated increased exponentially with the associated vaccination coverage, with a cost of 1.86 to achieve 25%, 2.51 for 50% coverage, and 3.19 for 70% coverage. Traditional vaccination methods failed to achieve sufficiently high vaccination coverages needed to interrupt sustained rabies virus transmission, whilst the technology-aided approach increased coverage above this critical threshold. Over successive campaigns, this difference is likely to represent the success or failure of the intervention in eliminating the rabies virus. Technology-aided vaccination should be considered in resource limited settings where rabies has not been controlled by traditional vaccination methods. The use of technology to direct health care workers based on near-real-time spatial data from the field has myriad potential applications in other vaccination and public health initiatives.